Pengaruh Kelas Hamil Metode Maryam terhadap Tingkat Kecemasan Ibu Hamil dalam Menghadapi Persalinan - Handayani, Sri; Fatma, Fitri (LPPM Akademi Kebidanan Harapan Ibu Pekalongan, 2025)
During the second and third trimesters of pregnancy, some mothers experience anxiety because they imagine the pain of the birth process, so they need support to face the birth. Pregnancy classes are one of the government's programs to reduce maternal mortality, while Maryam's method is an adoption of classes for pregnant women which prioritize Islamic values ​​in practice such as understa006Eding verses from the Holy Qur'an, consuming dates, and modifying pregnancy exercises with prayer movements. Research Objective to determine the effect of pregnancy classes using the Maryam method on the level of anxiety of pregnant women in the second and third trimesters in facing childbirth. Research method Quantitative research type with one group pretest-posttest design with a crossectional approach. The population was 33 respondents at TPMB Fitri Fatma Gondangrejo Karanganyar in April 2024, the sampling technique was purposive sampling. The sample for this research was pregnant women in the second and third trimesters, namely 30 respondents. Data was collected using the STAI Y-1 questionnaire sheet. Data analysis used the paired sample t-test. Research results a p-value of 0.011 (p-value < 0.05). Based on the research results, it can be concluded that there is an influence of the Maryam method of pregnancy classes on the level of anxiety of pregnant women in the second and third trimesters in facing childbirth at TPMB Fitri Fatma Karanganyar.